Prenatal Exposure to PM2.5 Oxidative Potential and Lung Function in Infants and Preschool- Age Children: A Prospective Study - Marsal, Anouk; Slama, Rémy; Lyon-Caen, Sarah; Borlaza, Lucille Joanna S.; Jaffrezo, Jean-Luc; Boudier, Anne; Darfeuil, Sophie; Elazzouzi, Rhabira; Gioria, Yoann; Lepeule, Johanna; Chartier, Ryan; Pin, Isabelle; et al. (Environmental health perspectives, 2023)
Fine particulate matter (PM2.5) has been found to be detrimental to respiratory health of children, but few studies have examined the effects of prenatal PM2.5 oxidative potential (OP) on lung function in infants and preschool children.BACKGROUNDFine particulate matter (PM2.5) has been found to be detrimental to respiratory health of children, but few studies have examined the effects of prenatal PM2.5 oxidative potential (OP) on lung function in infants and preschool children.We estimated the associations of personal exposure to PM2.5 and OP during pregnancy on offspring objective lung function parameters and compared the strengths of associations between both exposure metrics.OBJECTIVESWe estimated the associations of personal exposure to PM2.5 and OP during pregnancy on offspring objective lung function parameters and compared the strengths of associations between both exposure metrics.We used data from 356 mother-child pairs from the SEPAGES cohort. PM filters collected twice during a week were analyzed for OP, using the dithiothreitol (DTT) and the ascorbic acid (AA) assays, quantifying the exposure of each pregnant woman. Lung function was assessed with tidal breathing analysis (TBFVL) and nitrogen multiple-breath washout (N2MBW) test, performed at 6 wk, and airwave oscillometry (AOS) performed at 3 y. Associations of prenatal PM2.5 mass and OP with lung function parameters were estimated using multiple linear regressions.METHODSWe used data from 356 mother-child pairs from the SEPAGES cohort. PM filters collected twice during a week were analyzed for OP, using the dithiothreitol (DTT) and the ascorbic acid (AA) assays, quantifying the exposure of each pregnant woman. Lung function was assessed with tidal breathing analysis (TBFVL) and nitrogen multiple-breath washout (N2MBW) test, performed at 6 wk, and airwave oscillometry (AOS) performed at 3 y. Associations of prenatal PM2.5 mass and OP with lung function parameters were estimated using multiple linear regressions.In neonates, an interquartile (IQR) increase in OPvDTT (0.89 nmol/min/m3) was associated with a decrease in functional residual capacity (FRC) measured by N2MBW [β=-2.26mL; 95% confidence interval (CI): -4.68, 0.15]. Associations with PM2.5 showed similar patterns in comparison with OPvDTT but of smaller magnitude. Lung clearance index (LCI) and TBFVL parameters did not show any clear association with the exposures considered. At 3 y, increased frequency-dependent resistance of the lungs (Rrs7-19) from AOS tended to be associated with higher OPvDTT (β=0.09 hPa×s/L; 95% CI: -0.06, 0.24) and OPvAA (IQR=1.14 nmol/min/m3; β=0.12 hPa×s/L; 95% CI: -0.04, 0.27) but not with PM2.5 (IQR=6.9 μg/m3; β=0.02 hPa×s/L; 95% CI: -0.13, 0.16). Results for FRC and Rrs7-19 remained similar in OP models adjusted on PM2.5.RESULTSIn neonates, an interquartile (IQR) increase in OPvDTT (0.89 nmol/min/m3) was associated with a decrease in functional residual capacity (FRC) measured by N2MBW [β=-2.26mL; 95% confidence interval (CI): -4.68, 0.15]. Associations with PM2.5 showed similar patterns in comparison with OPvDTT but of smaller magnitude. Lung clearance index (LCI) and TBFVL parameters did not show any clear association with the exposures considered. At 3 y, increased frequency-dependent resistance of the lungs (Rrs7-19) from AOS tended to be associated with higher OPvDTT (β=0.09 hPa×s/L; 95% CI: -0.06, 0.24) and OPvAA (IQR=1.14 nmol/min/m3; β=0.12 hPa×s/L; 95% CI: -0.04, 0.27) but not with PM2.5 (IQR=6.9 μg/m3; β=0.02 hPa×s/L; 95% CI: -0.13, 0.16). Results for FRC and Rrs7-19 remained similar in OP models adjusted on PM2.5.Prenatal exposure to OPvDTT was associated with several offspring lung function parameters over time, all related to lung volumes. https://doi.org/10.1289/EHP11155.DISCUSSIONPrenatal exposure to OPvDTT was associated with several offspring lung function parameters over time, all related to lung volumes. https://doi.org/10.1289/EHP11155.